Data on an Austrian Company's Productivity in the Pre-Covid-19 Era, During the Lockdown and After Its Easing: To Work Remotely or Not? - Beno, Michal; Hvorecky, Jozef (Frontiers in Communication, 2021)
The Covid-19 crisis across the world has increased the proportion of e-working. The transition from cubicles to the home office raised many questions on adoptions of companies to coming conditions. Our paper provides recent evidence on the size of this move, its impact on the workplace evolution, productivity and the future prevalence of the face-to-display workplace after the easing of the lockdown. It uses data from 154 employees of an Austrian company obtained using online surveys conducted during the pre-Covid-19 era as well as during its different stages. According to our data, there are significant differences in the proportions of workers in the office and at home during different periods. After the lockdown, there was a significant increase in the number of those who had started working at home. Compared to the times prior the lockdown, they have got a tolerant attitude to their work from home and believed that their productivity might remain the same. On the other hand, our data indicate that for many of them their change was an unavoidable necessity and their return to the traditional workplace is their preference. During the lockdown, more than half of those who previously worked in their office premises started working from home. After the lockdown only a third of them did. We therefore studied the issues related to their productivity and its limits. There are three important reasons for the fall in productivity related to e-working: 1) Providing childcare/home schooling, pet sitting and/or care for others while working (28.41%); 2) Work-from-home routine (26.13%); and 3) Having less work to do (21.59%). The results suggest that more than one fifth (22.08%) want to continue working from home permanently, about one third (35.06%) more frequently than before, more than a quarter (27.92%) sometimes and just one seventh (14.94%) not at all.